2020
DOI: 10.1002/cft2.20049
|View full text |Cite
|
Sign up to set email alerts
|

Impact of poultry litter application on alfalfa grown in Mississippi

Abstract: Alfalfa (Medicago sativa L.) production in the Coastal Plain of the southeastern United States requires enhanced soil fertility management to capitalize on increased dry matter yield and nutritive value. Poultry litter (PL) is an abundant fertilizer source that has been recognized as an economical choice for pasture and hay production. A field trial was established in east‐central Mississippi in which PL and inorganic fertilizer sources were compared in three alfalfa cultivars in 2018 and 2019. Fertilizer trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…(1992) and Rushing et al. (2020) reported significant stand reductions after 2 yr of production in southeastern Louisiana and east‐central Mississippi, respectively. In terms of grazing, Cassida et al.…”
Section: Forage Systems In the Southeastern United Statesmentioning
confidence: 96%
See 1 more Smart Citation
“…(1992) and Rushing et al. (2020) reported significant stand reductions after 2 yr of production in southeastern Louisiana and east‐central Mississippi, respectively. In terms of grazing, Cassida et al.…”
Section: Forage Systems In the Southeastern United Statesmentioning
confidence: 96%
“…Stringer et al (1996) reported CP values of interseeded 'Cimarron' alfalfa without N fertilization exceeded those of 'Tifton-44′ bermu'dagrass monoculture at the 400 lb N acre −1 rate. Morris et al (1992) and Rushing et al (2020) reported significant stand reductions after 2 yr of production in southeastern Louisiana and east-central Mississippi, respectively. In terms of grazing, Cassida et al (2006) reported extended grazing seasons when alfalfa was interseeded into bermudagrass compared with alfalfa as a monoculture.…”
mentioning
confidence: 99%
“…Poultry litter is an important source of organic fertilizer that is normally surfaceapplied on fields for the improvement of soil quality and increased yield in agricultural production. This is particularly common for pastures and hayfields, where different types of forages are cultivated for ruminant and non-ruminant animal nutrition [1][2][3]. Poultry litter contains valuable nutrients, including trace and non-trace metals, and its application can enhance soil productivity and improve soil quality by improving aggregate formation and stability.…”
Section: Introductionmentioning
confidence: 99%